Saliva and Serum Cytokine Profiles During Oral Ulceration in Behçet’s Disease - Novak, Tanya; Hamedi, Mojgan; Bergmeier, Lesley Ann; Fortune, Farida; Hagi-Pavli, Eleni (Frontiers in Immunology, 2021)
Behçet’s disease (BD) is a chronic, multi-systemic disorder that is typified by recurrent oral and genital mucocutaneous lesions, uveitis and vasculitis. The aetiology of BD is unknown however, both innate and adaptive immune system dysregulation has been implicated in pathogenesis with alteration in cytokine profiles reported in serum. No studies have investigated salivary cytokines in BD, despite more than 90% of BD patients first presenting with oral ulceration. The aim of this study was to investigate cytokine levels in matched serum and saliva of BD, recurrent aphthous stomatitis (RAS) and healthy controls (HCs) to explore whether differential cytokine profiles in serum and saliva could provide a panel of cytokines with diagnostic and therapeutic potential for BD. Concentrations of 12 cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12 p70, IL-17A, IFN-γ, TNF-α,TNF-β) were measured using the Human Th1/Th2 11-Plex FlowCytomix™ kit with IL-17A, in BD (N=20), RAS (N=6) and HCs (N=10). There was indeed a differential range of cytokines in serum and saliva with the majority of cytokine levels higher in saliva. The most prevalent salivary cytokines were IL-1β, IL-2, IL-8, IL-10 and TNF-α present in all samples in contrast to serum where the most prevalent cytokine detected was IL-8 (91.9%). The least abundant cytokine was IFN-γ in both saliva (43.2%) and serum (2.7%). Compared to HCs, saliva from BD patients with ulcers (BD-MA) had significantly higher levels of IL-1β (p=0.01), IL-8 (p=0.02), TNF-α (0.004) and IL-6 (0.01) as did patients without ulcers (BD-MQ) IL-1β (p=0.05), IL-8 (p=0.04) and TNF-α (0.05). During active (BD-RE) and quiet (BD-Q) disease episodes salivary IL-β and TNF-α were also significantly higher with IL-8 significantly higher only in BD-Q (p=0.02). BD oral ulcers signify a potential reactivation of systemic inflammation therefore identifying cytokines released during ulceration might lead to targeted drug therapy to prevent recurrent oral ulcers and therefore disease relapse. This is the first study to report salivary cytokine levels in BD therefore since levels are higher in saliva, cytokine profiling of BD saliva may provide an alternative less invasive and sensitive procedure for monitoring disease activity and progression more frequently in patients.